Do a few tools necessarily mean a few people? A techno-morphological approach to the question of group size at Gesher Benot Ya'aqov, Israel. Issue 128 (March 2019) - Herzlinger, Gadi; Goren-Inbar, Naama
Abstract: The question of Paleolithic group size has been addressed by scholars in many disciplines applying different methods. In our study we apply a novel analytical approach in an attempt to assess the group size of hominins that occupied the Acheulian site of Gesher Benot Ya'aqov, Israel (GBY). Within this framework, we subjected the handaxe assemblages from several archaeological horizons at the site to a morpho-technological analysis. The analysis combined high-resolution three-dimensional geometric morphometric analysis with typo-technological attribute analysis to assess the inter- and intra-assemblage morpho-technological variability. The analysis was also applied to an experimental handaxe assemblage produced by an expert knapper. The results of the analysis show high morphological homogeneity coupled with high technological variability in each of the archaeological assemblages. This pattern is highly indicative of the work of expert knappers, as is also suggested by the comparison between the archaeological and experimental assemblages. The high density of archaeological remains in some of the GBY occupations and their pristine taphonomic condition provide additional support for the involvement of large groups of hominins, although some horizons are far poorer in archaeological remains and hence do not allow such an interpretation. Nevertheless, the fact that in all assemblages the handaxes show the same techno-morphological pattern indicates that they were all produced by expert knappers. As shown by numerous models and ethnographic data, the presence of experts can be viewed as an indication of large and socially complex societies. Thus, although some of the GBY occupations were not formed by large groups, the smaller groups whose activities are recorded were very likely to be part of larger, socially complex cultural groups. This variability in occupational intensity is interpreted as representing an aggregation-dispersal mechanism, similar to those documented in many hunter-gatherer societies.